Economic Burden and Predictors of Cost Variability Among Adult Cancer Patients at Comprehensive Specialized Hospitals in West Amhara, Northwest Ethiopia, 2019 - Hagos, Asebe (Cancer Manag Res, 2020)
BACKGROUND: Cancer is the second leading cause of death in the world and accounts for 5.8% of deaths in Ethiopia. High out-of-pocket payment for the cost of illness of cancer could be linked to the low adherence to cancer treatment. This study aimed to assess the economic burden and predictors of cost variability among adult cancer patients at comprehensive specialized hospitals in West Amhara, Northwest Ethiopia. METHODS: An institutional-based cross-sectional study was conducted from January to February 2019 at the University of Gondar and Felege Hiwot hospitals. The cost of illness of cancer was estimated using a bottom-up micro-costing approach. Direct costs of illness of cancer were measured by calculating out-of-pocket expenditure. The indirect costs were estimated using human capital model approach. Multiple linear regression was used to identify the predictors for the log-transformed data. Unstandardized β-coefficient with 95% CI and p-value < 0.05 were used to declare factors associated with cost of illness of cancer. RESULTS: The mean cost of cancer illness among adult patients was US$ 1103.7 ±33.2, and median cost was US$ 951.0 with IQR of 822.1. Factors such as urban residents (β = 0.147; 95% CI: 0.047, 0.246), distance (β = 0.0007; 95% CI: 0.0002, 0.001), married (β = 0.125; 95% CI: 0.037, 0.212), higher education (β = 0.318; 95% CI: 0.202, 0.435), buying drugs at private facilities (β = 0.134; 95% CI: 0.026, 0.243), richest households (β = 0.320; 95% CI: 0.143, 0.496) and frequent cycles of chemotherapy (β = 0.093; 95% CI: 0.061, 0.125) were positively associated with cost, while being female patients (β = −0.144; 95% CI: − 0.210, − 0.018) were negatively associated. CONCLUSION: The cost of illness of cancer was high. The government, therefore, should expand health insurance and invest an additional budget to safeguard patients from financial catastrophic shock.